Repeated biopsies in patients with prostate cancer on active surveillance: clinical implications of interobserver variation in histopathological assessment. (16th August 2014) - Thomsen, Frederik B.; Marcussen, Niels; Berg, Kasper D.; Christensen, Ib J.; Vainer, Ben; Iversen, Peter; Brasso, Klaus
Abstract : Objective: To investigate the clinical implications of interobserver variation in the assessment of re‐biopsies obtained during active surveillance (AS) of prostate cancer. Patients and Methods: In all, 107 patients with low‐risk prostate cancer with 93 diagnostic biopsy sets and 109 re‐biopsy sets were included. The International Society of Urological Pathology 2005 Gleason scoring system was used for the histopathological assessment of all biopsies. Three different definitions of histopathological progression were applied. Unweighted and linear weighted Kappa (κ) statistics were used to compare the interobserver agreement. Results: The overall Gleason score agreement was 68.8% with a weighted κ of 0.670. The interobserver agreement was 79.6% for meeting the AS selection criteria. According to the three progression definitions applied, overall agreement was between 80.7% and 89.0% with weighted κ values of 0.746–0.791. Treatment recommendations would have changed in up to 10.1% (95% confidence interval 5.4–17.7%) of the 109 re‐biopsy sets. Conclusion: Kappa statistics showed strong agreement between the histological evaluations. However, up to 10% of patients on AS would receive a different treatment recommendation depending upon which histopathological evaluation of re‐biopsies was used for treatment planning.